Análisis Jurídico y Doctrinario al Derecho de No Revictimización en el Procedimiento Expedito para la Violencia Contra la Mujer y Miembros del Núcleo Familiar - Ramos Ramos., María de los Ángeles (2024)
This research, entitled “Analysis of the Right of Non-Revictimization in the Expedited Procedure for Violence against Women and Family Members”, focuses on the study and analysis of the expedited procedure implemented in Ecuador to deal with cases of violence against women and family members. This procedure seeks to guarantee a rapid and effective response to these situations of violence, avoiding the re-victimization of the victims. The general objective of this research is to evaluate the effectiveness and challenges of the expedited procedure in the protection of victims' rights and their non-revictimization. A comparative analysis is made with the legal frameworks of Spain, Mexico and Argentina to identify good practices and areas for improvement. The methodology used in this study includes documentary review, normative analysis and interviews with legal professionals and victims of violence. The results show that, although the expedited procedure has improved the judicial response, there are still significant challenges in the effective implementation of protection measures and the awareness of justice operators. It is concluded that it is essential to strengthen the training of judicial officials, improve inter-institutional coordination and promote greater social awareness to ensure the empowerment and protection of victims of gender-based violence.